2022
DOI: 10.3390/jintelligence10040115
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Emotional Intelligence on Domain-Specific Creativity: The Mediating Role of Resilience and the Moderating Effects of Gratitude

Abstract: Creativity incorporates both domain-general and domain-specific ideas. While previous studies have explored the impact of emotional intelligence (EI) on creativity in both domains, a consensus has not been reached, and the mechanism is currently unclear. In the present study, we examined which aspect of creativity EI was most strongly associated with in a group of undergraduates. Moreover, we explored the moderated mediation effect between EI and domain-specific creativity. In Study 1, 532 undergraduates compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 103 publications
1
6
0
Order By: Relevance
“…When graduate students face academic challenge stress, overcoming the stress generates positive emotional resources that promote resilience. According to emotional motivation theory ( Gable and Harmon-Jones 2010 ), people with more resilience tend to maintain a positive steady state and come up with creative problem-solving solutions ( Avey et al 2011 ; Tong et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…When graduate students face academic challenge stress, overcoming the stress generates positive emotional resources that promote resilience. According to emotional motivation theory ( Gable and Harmon-Jones 2010 ), people with more resilience tend to maintain a positive steady state and come up with creative problem-solving solutions ( Avey et al 2011 ; Tong et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the authors, the lack of engagement may also be due to the psychophysical characteristics of the player, specifically the level of emotional intelligence. It can have a positive impact on the participant's engagement in co-creation by improving communication, enhancing cooperation, and increasing creativity and ease of problem-solving (Delpechitre et al, 2018;Tong et al, 2022). This set of skills makes individuals more engaged in the co-creation process, as it can help them build relationships, generate new ideas as well as perform better.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent research has shown a connection, between employees emotional awareness and personality with creativity as highlighted in studies by Xu et al (2019) Geher et al (2017 Tong et al (2022). Sundquist & Lubart (2022).…”
Section: Introductionmentioning
confidence: 98%
“…Those who can display their creativity often experience increased confidence, motivation, and job satisfaction. This creative expression fosters greater emotional awareness, both of oneself and others, leading to better interpersonal relationships at work (Tong et al, 2022).…”
Section: Introductionmentioning
confidence: 99%